Hypothesizing That Neuropharmacological and Neuroimaging Studies of Glutaminergic-Dopaminergic Optimization Complex (KB220Z) Are Associated With "Dopamine Homeostasis" in Reward Deficiency Syndrome (RDS). (21st March 2017) - Blum, Kenneth; Febo, Marcelo; Fried, Lyle; Li, Mona; Dushaj, Kristina; Braverman, Eric R.; McLaughlin, Thomas; Steinberg, Bruce; Badgaiyan, Rajendra D.
ABSTRACT: Background : There is need for better treatments of addictive behaviors, both substance and non-substance related, termed Reward Deficiency Syndrome (RDS). While the FDA has approved pharmaceuticals under the umbrella term Medication Assisted Treatment (MAT), these drugs are not optimal. Objectives : It is our contention that these drugs work well in the short-term by blocking dopamine function leading to psychological extinction. However, use of buprenorphine/Naloxone over a long period of time results in unwanted addiction liability, reduced emotional affect, and mood changes including suicidal ideation. Methods : We are thus proposing a paradigm shift in addiction treatment, with the long-term goal of achieving "Dopamine Homeostasis." While this may be a laudable goal, it is very difficult to achieve. Nevertheless, this commentary briefly reviews past history of developing and subsequently, utilizing a glutaminergic-dopaminergic optimization complex [Kb220Z] shown to be beneficial in at least 20 human clinical trials and in a number of published and unpublished studies. Results : It is our opinion that, while additional required studies could confirm these findings to date, the cited studies are indicative of achieving enhanced resting state functional connectivity, connectivity volume, and possibly, neuroplasticity. Conclusions/Importance : We are proposing a Reward Deficiency Solution System (RDSS) that includes: Genetic Addiction Risk Score (GARS); Comprehensive Analysis of Reported Drugs (CARD); and a glutaminergic-dopaminergic optimization complex (Kb220Z). Continued investigation of this novel strategy may lead to a better-targeted approach in the long-term, causing dopamine regulation by balancing the glutaminergic-dopaminergic pathways. This may potentially change the landscape of treating all addictions leading us to the promised land.